Neural mechanisms of musical structure and tonality, and the effect of musicianship - Jiang, Lei; Zhang, Ruiqing; Tao, Lily; Zhang, Yuxin; Zhou, Yongdi; Cai, Qing (Frontiers in Psychology, 2023)
The neural basis for processing musical syntax has previously been examined almost exclusively in classical tonal music, characterized by a strictly organized hierarchical structure. The present study investigated the neural mechanisms for processing musical structure across genres varying in tonality – classical, impressionist, and atonal music – and, in addition, examined how musicianship modulates such processing. Results showed that, first, the dorsal stream including the bilateral inferior frontal gyrus and superior temporal gyrus played a key role in the perception of tonality. Second, right frontotemporal regions were crucial in allowing musicians to outperform non-musicians in musical structure processing; musicians also benefited from a cortical-subcortical network including pallidum and cerebellum, suggesting increased auditory-motor interactions in musicians than in non-musicians. Third, left pars triangularis carried out online computations independently of tonality and musicianship, whereas right pars triangularis tended to be sensitive to tonality and partly dependent on musicianship. Finally, unlike tonal music, the processing of atonal music could not be differentiated from that of scrambled notes, both behaviorally and neurally, even among musicians. The present study highlights the importance of studying varying music genres and experience levels. It also provides a better understanding of musical syntax/musical structure, tonality processing, and how such processing is modulated by music experience.